Rare Earth Doping of Topological Insulators: A Brief Review of Thin Film and Heterostructure Systems (Phys. Status Solidi A 8∕2019). Issue 8 (23rd April 2019) - Hesjedal, Thorsten
Abstract : Topological Insulators Long‐range ferromagnetic ordering in rare‐earth doped topological insulators are achieved for first the first time. Proximity coupling and interfacial effects, multiplied in artificial heterostructures, are used to engineer the electronic and magnetic properties of a Dy:Bi2 Te3 /Cr:Sb2 Te3 thin film heterostructure, introducing long‐range magnetic order in high‐moment Dy:Bi2 Te3 . More details can be found in article number 1800726 by Thorsten Hesjedal. TEM images courtesy of Dr. Vlado Lazarov (University of York).